The interactive world of severe mental illness : case studies of the U.S. mental health system /: case studies of the U.S. mental health system. (2015) - Semmelhack, Diana; Ende, Larry; Freeman, Arthur; Hazell, Clive; Barron, Colleen L; Treft, Garry L
No abstract available